Influência de reservatórios sobre a diversidade funcional do fitoplâncton da planície de inundação do alto rio Paraná - Paula, Aline Caroline Magro de (2016)
Building reservoirs is a major cause of loss of biological diversity in floodplain. Diversity loss affects ecosystem processes and services, so it is fundamental to determine the factors that affect species diversity. Functional diversity (FD) is a mechanistic approach to determine the factors that influence the biological communities. The aim of this study was to evaluate the phytoplankton functional diversity of the Upper Paraná River and their associated lakes in the Upper Paraná River floodplain, downstream of a cascading of reservoirs. We tested the following hypothesis: i) DF is mainly influenced by the hydrological regime of the Paraná River; ii) there is a DF gradient along the stretch studied in the Upper Paraná River, being the highest values in the more distant stations from Porto Primavera reservoir. Quarterly samplings were carried in the Paraná River and associated lakes (between Porto Primavera and Itaipú reservoirs) in the years 2013 and 2014. DF was calculated by the Rao?s quadratic entropy, functional richness (FRic) and functional evenness (FEve). Principal Component Analysis (PCA) was performed to verify the environmental variability. The significance of the separation shown on axis was tested by Analysis of Variance (ANOVA). Multiple Linear regression was performed to investigate the predictors of DF. To determine which factors affect the structure of phytoplankton functional traits we carried out a Redundancy Analysis (RDA). The DF values were low in all stations and the models tested to the River showed significant correlation with total phosphorus. There were registered low FRic and FEve values, indicating less complementary niche and dominance traits maybe caused by biotic homogeneity, as a consequence of the reservoir cascade. In despite of the absence of significant differences between stations, the DF responded to gradient of productivity from Paraná River, with higher values in the most distant stations. Environmental conditions favorable for phytoplankton development in lentic environments provided high density values and dominance of functional traits. The traits dominance influenced low DF values. The influence of the Parana River on the DF of Lakes was evident due the lakes with lower connectivity had the lowest values, especially in higher fluviometric level. Reduction of connectivity between river and lakes due to alterations on the floods magnitude of Parana River, probably influenced the DF in these environments.